ANALISIS KEWENANGAN DAN TANTANGAN KOMISI YUDISIAL DALAM PENGAWASAN KODE ETIK HAKIM PENGADILAN AGAMA DI SULAWESI SELATAN - Khalil Mushaddiq; Nurfaika Ishak; Muhammad Yaasiin Raya (Universitas Islam Negeri Alauddin Makassar, 2025)
This study aims to analyze the authority of the Judicial Commission in supervising the code of ethics of judges in Religious Courts, as well as the challenges faced in its implementation. The research employs a qualitative approach with field research methods, utilizing primary data from interviews with Judicial Commission officials and secondary data from relevant legislation and official documents, which were analyzed descriptively. The findings reveal that the South Sulawesi Judicial Commission Liaison serves as an extension of the central Judicial Commission, with authority limited to monitoring judicial behavior, the application of the Code of Ethics and Guidelines for Judicial Conduct (KEPPH), and courtroom proceedings. The main obstacle lies in the broad scope of supervision compared to the limited number of personnel, only four members, necessitating a strategy of building community networks to obtain information on suspected ethical violations. The study recommends two measures: first, increasing the number of liaison members in each region; and second, strengthening the authority of the Judicial Commission so that it not only provides recommendations but also possesses executorial power in enforcing judicial ethics.